EVALUASI KELAYAKAN YANG MEMPERTIMBANGKAN KETIDAKPASTIAN PADA INVESTASI MESIN PRODUKSI BOTOL PADA PT. SPT JEMBER - Putra, Mohamad Hengki Riaran; Fadah, Isti; Sukarno, Hari (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2016)
Abstract: This study examines the feasibility of the investment plan. The data used were primary data that consisted of the data of investment planning and cash flow estimation data for the upcoming period, and secondary data generated from the company's financial data. Investment valuation methods used are the discounted payback period, net present value (NPV), internal rate of return (IRR), modified rate of return (MIRR), profitability index (PI), and transfer pricing. Results of analysis show that the discounted payback period is less than 3 years, NPV is Rp. 441.032.525, IRR is 56.2%, MIRR is 47.9%, PI is 1.7, and the cost calculation of company’s own production and price transfers shows that the company’s own production (investment in new machines) is more profitable. According to the project acceptance criteria, the results of the analysis indicate that the investment plan of PTSPT is feasible. Keywords: Investment,Uncertainty, Payback Period, NPV, IRR, MIRR, and PI